Technologies of studying the lyrics of Abai Kunanbaev in higher educational schools.. (Eurasian Journal of Philology Science and Education, 2022)
In the article the innovative technologies, used in the modern educational process, are considered. The author reveals their functions, role and practical significance. Great attention is paid to innovative technologies, used in the process of teaching of philological disciplines. The material of the study is the work of the classic of Kazakh literature Abai Kunanbaev. The actuality of this theme is determined by the need to increase students’ interest in the heritage of the great poet, thinker and philosopher, deepen their theoretical knowledge of his poetry and develop practical skills in analyzing of artistic works. In the article the importance of innovative technologies in revealing new aspects of A. Kunanbaev’s lyrics, in improving the quality of the educational process, in the search for new organizational forms of lectures and practical classes is substantiated. The objects of studing are the methods and techniques of teaching the heritage of the classic of Kazakh literature in higher educational schools. In the article the basic principles of the analysis of poetic works of A. Kunanbaev in the process of conducting lectures and practical classes are revealed. Based on the systematization of works, devoted to modern pedagogical technologies, a specific methodology for studying the artistic heritage of the classic of Kazakh literature is proposed. In the article the practical significance of innovative technologies is revealed. The ways and features of using such methods as case-study, contextual and programmed learning, brainstorming, telecommunicational project, game techniques, technology for the development of critical thinking are indicated. On the example of the poetic works of Abai Kunanbaev, the effectiveness and prospects of their application in the study of artistic creativity, understanding the nature of verbal art, understanding the writer’s worldview are substantiated.